Pengaruh Kebijakan Pemasaran Terhadap Kepuasan Konsumen Baso Solo Putra Lawu - Yulianita Anderiyani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The study was commissioned to know the marketing policies on customer satisfaction at Bakso Solo Putra Lawu. The kind of research used in this study is the quantitative approach by taking on a population of consumer who bought in the Bakso Solo Putra Lawu. The variable was customer satisfaction marketing, data collection was obtained through the online distribution of questionnaires (e-questionnaires) taken in this study as many as 92 of the respondents in the dedicated Bakso Solo Putra Lawu who bought consumed the products. The sampling teachique used is purposive probability sampling. Keywords: Marketing policy, Consumer satisfaction